Game Burung Rangkong Terbang Sebagai Pengenalan Satwa Liar Burung Yang Dilindungi Di Indonesia - Hari Agung Budi Santoso; Hanif Al Fatta; M. Suyanto (Universitas Janabadra, 2022)
Birds are one of the types of wild animals in nature whose diversity continues to grow. Based on the records of Burung Indonesia in 2017, there were 1769 bird species identified in the country, from the previous 1672 species. Apart from catch and trade, deforestation is one of the factors that greatly affects the threat status of bird populations in nature. An example of the species affected is the hornbill due to habitat destruction and forest encroachment actions that continue to occur, since 2015 the status of this bird has skyrocketed to critical until now. Apart from encroachment and conversion of forests into plantations, the hornbill has also become an international trade commodity and is massively hunted in its natural habitat. Various threats that may occur due to reduced forest and biodiversity will have an impact on the hornbill. One of the conservation efforts is to introduce the hornbill species of wildlife to the community. The Flying Hornbill Game is a 2D game with an action game genre that requires players to use reflexes, accuracy, and the right timing to complete a challenge. as a result of the player's score. This study applies the Game Design Document (GDD) method in building a flying hornbill game application as a means of introducing protected hornbill to the public.